Family as the Patient’s Voice in Nurse-Patient Interaction - Anduquia Vásquez, Paula Andrea; Ramírez Barrientos, Adriana Maria; Lopera Betancur, Martha Adiela; Forero Pulido , Constanza; Córdoba Pérez, Luisa Fernanda (Revista Cuidarte, 2020)
Introduction: Families experience a major challenge when a next of kin is admitted to hospital as family dynamics are forced to change in terms of duties and roles. Qualitative research has been conducted with family members who supported one of their next of kin during their hospitalization. Family members were defined as those who had shared a common history with patients. Objective: To understand the meaning given by families to the patient’s voice role in the interaction with nurses during hospitalization. Materials and Methods: An ethnographic approach was used. Complete information was collected from 10 interviews with adults. Strict criteria and ethical principles were also applied. Results: Families consider that their right is to be the patient’s voice to interact with nurses, assuming it as one of their caregiving functions. To this end, nurses must respond to the call, assist, accompany and provide patients with minimal care required, primarily related to physical care, so they can demonstrate their human qualities, recognize patients’ needs and communicate on the basis of truth and closeness when interacting with patients. Families expect that nurses would recognize and instruct them, as well as tell the truth and be close to them. Conclusions: Families are the patient’s voice as a matter of connatural right, assuming patients’ care supported by nurses, who are in charge of building trust and providing good care.How to cite this article: Anduquia Vásquez Paula Andrea, Ramírez Barrientos Adriana, Lopera Betancur Martha Adiela, Forero Pulido Constanza, Córdoba Pérez Luisa Fernanda. La familia es la voz del paciente en la interacción con la enfermera Revista Cuidarte. 2020;11(3):e1015. http://dx.doi.org/10.15649/cuidarte.1015
Keywords: Family Relations; Nursing Care; Patients; Retention in Care